(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study empirically examines the impact of Artificial Intelligence (AI) on audit quality in emerging markets. Based on survey data from 370 audit professionals analyzed using Structural Equation Modeling (SEM), the research assesses how AI dimensions—including Robotic Process Automation (RPA), Machine Learning (ML), Anomaly Detection (AD), and Explainable AI (XAI)—affect audit quality, measured by efficiency, accuracy, and auditor independence. The findings confirm a significant positive impact, as anomaly detection enhances accuracy, machine learning improves efficiency and independence, and explainable AI is crucial for building auditor trust in AI-derived evidence. The study offers an evidence-based framework for audit firms and regulators, contributing to the literature on technology adoption in professional services.